Effects of bio-banding upon physical and technical performance during soccer competition: A preliminary analysis - Abbott, W.; Williams, S.; Brickley, G.; Smeeton, N. J. (Sports, 2019)
Bio-banded competition has been introduced to address the variation in physical maturity within soccer. To date, no research has investigated the effect of bio-banded competition relative to chronological competition. The current study investigated the effect of bio-banding upon physical and technical performance in elite youth soccer athletes. Twenty-five male soccer athletes (11-15 years) from an English Premier League soccer academy participated in bio-banded and chronological competition, with physical and technical performance data collected for each athlete. Athletes were between 85-90% of predicted adult stature, and sub-divided into early, on-time and late developers. For early developers, significantly more short passes, significantly less dribbles and a higher rating of perceived exertion (RPE) were evident during bio-banded competition compared to chronological competition (p < 0.05). Significantly more short passes and dribbles, and significantly fewer long passes were seen for on-time developers during bio-banded competition (p < 0.05). For late developers, significantly more tackles, and significantly fewer long passes were evident during bio-banded competition (p < 0.05). No significant differences in physical performance were identified between competition formats. Results demonstrated that bio-banded competition changed the technical demand placed upon athletes compared to chronological competition, without reducing the physical demands. Bio-banded competition can be prescribed to athletes of differing maturation groups dependent upon their specific developmental needs.